Effect of adding artichoke (Cynara scolymus L.) extract to the water or the diet on the production performance and physiological traits of broilers (Texas Journal of Agriculture and Biological Sciences, 2022)
The experiment was carried out in the poultry field of the Department of Animal Resources Sciences/College of Agriculture/University of Diyala for the period from 4/9/2021 to 14/10/2021, to study Effect of adding artichoke extract to water and diet as an antioxidant in broiler chickens and its effect on physiological and carcass traits, 225 unsexed Ross 308 hybrid broiler chicks were used at the age of one day. The chicks were randomly distributed from the first day of their reception to five experimental treatments with three replications for each treatment (15 birds/repeat), and the experimental treatments were T1 = (treatment The control) provided a standard diet without addition, T2 = a standard diet to which 75 mg/l artichoke extract was added, T3 = a standard diet to which 150 mg/l artichoke extract was added, T4 = a standard diet to which 2g/kg was added to an artichoke leaf extract. Artichoke, T5 = a standard ration to which 3 g/kg of artichoke extract is added. Comparing the results of the experiment with a significant effect when adding different levels of artichoke leaf base to water and Ross 308 broiler for 1-2 days in the weight of the normal and cleaned carcass with the third treatment T3 better for weight compared to the treatment treatment as well as the results have a significant effect. When different levels of artichoke leaf powder were added to Ross 308 broiler broiler feed and water for 42-1 period in the humoral level, it was significantly superior to treatment T5 (P < 0.05) and the highest volume level and treatment against Newcastle disease was recorded at 4,606.25. The results also showed that there were statistically significant differences regarding the volumetric standard of antibodies to bronchitis disease, where T5 treatment excelled in recording the highest volumetric standard of antibodies, thus 6105.50.